The Effect of the Limit Accuracy in the Calculation of the Mean and Standard Deviation. - Ruiz L., Edgar (2001)
When calculations are performed on a computer is the problem of the accuracy or acuracidad of these. Paraanalizar this problem calculate the mean and standard desciación with a hypothetical set of test data are examined. The programming language C + + is used, using two different algorithms in the calculation; came forward, and others to conclude that acuracidad depends on the algorithm used and the ability to represent data from a computer.